The Prospects of gene introgression from crop wild relatives into cultivated lentil for climate change mitigation - Rajpal, Vijay Rani; Singh, Apekshita; Kathpalia, Renu; Thakur, Rakesh Kr.; Khan, Mohd. Kamran; Pandey, Anamika; Hamurcu, Mehmet; Raina, Soom Nath (Frontiers in Plant Science, 2023)
Crop wild relatives (CWRs), landraces and exotic germplasm represent an important source of alien alleles and cryptic genetic variability hidden in their gene pools. The effective utilization of these useful crop traits’ reservoirs in breeding programs can provide the adaptive potential required to mitigate a plethora of abiotic and biotic stresses and reduction in crop yield arising due to global climatic changes. The advent of genome mapping and advanced high-throughput sequencing technologies representing the omics-era have helped identify many stress-responsive adaptive genes, quantitative trait loci (QTLs) and other useful crop traits in CWRs and their introgression in modern cultivars of many crops. In the pulse crop genus Lens, the genetic base of the cultivated varieties has become narrow due to recurrent selections. Most of the lentil breeding objectives such as higher yield, adaptation to abiotic stresses, and resistance to diseases are quantitative and require the identification of quantitative trait loci (QTLs) for marker-assisted selection (MAS) and breeding. The collection and characterization of wild Lens germplasm resources have offered new avenues for the genetic improvement and development of stress-tolerant climate-resilient lentil varieties with sustainable yield gains to meet future food and nutritional requirements. The recent generation of dense genomic linkage maps, large transcriptomic data sets, single nucleotide polymorphisms (SNPs), and expressed sequence tags (ESTs) have advanced lentil genomic research substantially. This review highlights the rapid strides undertaken in the characterization of genetic resources for useful alleles, construction of genetic and genomic linkage maps, QTLs identification related to important traits and new databases in traditionally bred genus Lens for future crop improvement.